Application of Multi-Item EOQ Method in Raw Material Inventory Control at Jofie Bakery and Cake Shop Medan - Hutahaean, Trisna D; Mardiningsih (Talenta Publisher, 2022)
Inventory of raw material is one of the factors in the production process. Whereas lack of material would result in a slowing down of production, excess of raw materials would result in increased storage and other costs. The purpose of this study was to identify and analyze the control of the supply of raw materials applied by jofie bakery & cake shop. The kind of research used was quantitative research. The data source in this study USES secondary data sources directly from the company. The result of study showed that the use of EOQ methods on companies was resulted in cheaper cost when compared with the methods used by the company, and there was a difference in cost-saving expenses at 3.5% on average.